2022
DOI: 10.21037/tcr-22-1544
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 affects tumor metastasis through epithelial-mesenchymal transition: a narrative review

Abstract: Background and Objective: Annexin A1 (annexin I, ANXA1), the first discovered member of the annexin superfamily, plays important roles in tumor development, invasion, metastasis, apoptosis and drug resistance based on tumor type-specific patterns of expression. The acquisition of the epithelialmesenchymal transition (EMT) characteristics is an essential mechanism of metastasis because they increase the mobility and invasiveness of cancer cells. Cancer invasion and metastasis remain major health problems worldw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 152 publications
(271 reference statements)
0
2
0
Order By: Relevance
“…Annexins, as supported by empirical evidence, play a pivotal role in mediating the processes of cancer cell invasion and metastasis. Their involvement is thought to be intricately linked with speci c intracellular signaling pathways, those that govern cellular growth, transformation, and the intricately regulated process of apoptosis 35 .…”
Section: Hence Deciphering the Underlying Biological Mechanisms Of Br...mentioning
confidence: 99%
“…Annexins, as supported by empirical evidence, play a pivotal role in mediating the processes of cancer cell invasion and metastasis. Their involvement is thought to be intricately linked with speci c intracellular signaling pathways, those that govern cellular growth, transformation, and the intricately regulated process of apoptosis 35 .…”
Section: Hence Deciphering the Underlying Biological Mechanisms Of Br...mentioning
confidence: 99%
“…Several studies have reported anti-inflammatory activity of ANXA1 [4] , [5] , [6] , and overexpression of ANXA1 in diabetic mice can relieve diabetes-induced kidney injury [7] . However, its overexpression is associated with several cancers [8] , [9] , [10] and antineutrophil cytoplasmic autoantibody-associated vasculitis [11] .…”
Section: Introductionmentioning
confidence: 99%